Climate classification by Thornthwaite (1948) humidity index in future scenarios for Maranhão State, Brazil - de Oliveira Aparecido, Lucas Eduardo; de Meneses, Kamila Cunha [UNESP]; Lorençone, Pedro Antonio; Lorençone, João Antonio; Moraes, Jose Reinaldo da Silva Cabral de; de Souza Rolim, Glauco [UNESP] (Springer Nature, 2022)
Air temperature and precipitation are the elements that most impact the development of plants and are essential for good agricultural planning. Thus, it aimed to evaluate climate change in Maranhão of Brazil using the Thornthwaite (Geographical Review 38:55–94, 1948) climate classification. It used historical series of precipitation and air temperature between 1980 and 2016, obtained by the National Institute of Meteorology of Brazil (INMET). Reference evapotranspiration (ETo) was estimated using the Thornthwaite (Geographical Review 38:55–94, 1948) method and thus calculated the water balance by Thornthwaite and Mather (Laboratory of Climatology 8:104) for all locations in the studied state. Thornthwaite (Geographical Review 38:55–94, 1948) moisture index was used to classify localities to their level of humidity or aridity. We used the scenarios RCP-2.6, RCP-4, RCP-6, and RCP-8.5 for analyzing twenty-first-century projections (2041–2060 and 2061–2080 periods). The average values of air temperature, rainfall, and reference evapotranspiration in the state of Maranhão were 27.30(± 0.53) °C, 1678.52 (± 377.70) mm, and 1067.98 (± 73.36) mm, respectively. The average annual climatic characterization of the state of Maranhão was 53.4 (± 38.6) mm of the soil water storage, 698.71 (81.07) mm of the water surplus, and 395.85 (± 65.91) mm of the water deficit. Maranhão had seven climatic indexes. The most prevalent in the state was the Humid (B1, B2, B3, and B4), with 61% of the entire territory. RCP2.6 and RCP 8.5 are the driest. RCP6.0 and RCP8.5 show the most significant changes in the current situation. The humidity index’s reduction will harm various economic activities in Maranhão, such as agriculture, livestock, and fishing.
Keywords: Climate change; Climate classification; Climate indices; Moisture index; Northeast Brazil